Comparison of Cannabinoid CB1 Receptor Binding in Adolescent and Adult Rats: A Positron Emission Tomography Study Using [18F]MK-9470. (11th December 2011) - Verdurand, Mathieu; Nguyen, Vu; Stark, Daniela; Zahra, David; Gregoire, Marie-Claude; Greguric, Ivan; Zavitsanou, Katerina
Abstract : Despite the important role of cannabinoid CB1 receptors (CB1 R) in brain development, little is known about their status during adolescence, a critical period for both the development of psychosis and for initiation to substance abuse. In the present study, we assessed the ontogeny of CB1 R in adolescent and adult rats in vivo using positron emission tomography with [ 18 F]MK-9470. Analysis of covariance (ANCOVA) to control for body weight that would potentially influence [ 18 F]MK-9470 values between the two groups revealed a main effect of age (F(1, 109)= 5.0, P = 0.02 ) on [ 18 F]MK-9470 absolute binding (calculated as percentage of injected dose) with adult estimated marginal means being higher compared to adolescents amongst 11 brain regions. This finding was confirmed using in vitro autoradiography with [ 3 H]CP55, 940 (F(10, 99)= 140.1, P < 0.0001 ). This ontogenetic pattern, suggesting increase of CB1 R during the transition from adolescence to adulthood, is the opposite of most other neuroreceptor systems undergoing pruning during this period.